Participatory socio-economic mapping of singosari village, Talang Padang District, Tanggamus Regency - Komang Ariyanto (Institute of Computer Science (IOCS), 2023)
Mapping socio-economic conditions in rural areas is used to see community needs and potential resources in order to find out which sectors need to be implemented and improved. This study aims to analyze the participatory mapping of socio-economic conditions in the village of Singosari, Tanggamus. This research uses a quantitative-descriptive method with a case study approach supported by qualitative data. The population in this study amounted to 464 heads of households and the sample was 30 households. In this study, the respondents and informants were farmer households and village government officials. Data collection was carried out through primary data through surveys, interviews, participatory observation, documentation, and literature studies on data related to participatory socio-economic mapping in rural areas. Data analysis used the interactive model Miles, Huberman and Saldana, and assisted with Microsoft Excel for processing survey data. The findings in this study are that the Singosari village has a variety of resources, both socio-economic and ecological. Even though the village has limitations in terms of education and health facilities, on the other hand, it has the potential for dryland farming which can be developed and become the focus of agricultural development program interventions. Recommendations/implications for the findings are that the results of the socio-economic mapping contain socio-economic data of villagers so that they can be used as a valid reference for making policies/programs. Socio-economic data is presented according to existing categories, arranged systematically, with explanations of the relationships between these categories, and can be read.